Utilization Of Maggot For The Cleanliness Of The Parung Bogor Traditional Market - Pratama, Dendi Anugrah; Wahyunengsih (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2023)
Waste is divided into two types, namely organic waste and inorganic waste. This organic waste consists of easily decomposed waste. Meanwhile, inorganic waste is waste that is quite difficult to decompose and must be assisted by engine power. The accumulation of waste in landfills is due to our lack of knowledge to decompose and process this waste. So that the waste is not too much.Â Â It should be noted that maggot is a caterpillar of the Black Soldier Fly type. This type of fly is different from the flies that we often find. Because the Black Soldier Fly is a type of fly that does not spread harmful bacteria. These BSF flies are black and more like wasps or bees. In addition to breaking down organic waste, this caterpillar can also be used as animal feed. Both poultry and fish farming. This caterpillar has high protein to nourish and fatten livestock. And the most important thing is that livestock will not be exposed to harmful bacteria. Because these flies are safe and do not spread harmful bacteria.Traditional markets are places where goods or staple goods such as groceries are exchanged. The groceries that are traded are organic foods for daily needs. These items will later produce piles of organic waste which will definitely cause disease and a very pungent odor. Therefore, the need for action to eliminate the problem. For the sake of bringing comfort together.Therefore, we analyze organic waste management methods that will have high economic value and be sustainable. Maggot cultivation aims to overcome market problems by turning organic waste into maggot larvae feed so that maggot larvae can be of value and the used feed can be used for planting media and fertilizer. So that the decomposition of organic waste has more economic value.Therefore, let's start learning to cultivate maggot to empower market organic waste and household organic waste to become more economically valuable.